Analisis determinan kemiskinan di Provinsi Jawa dan Bali - Wulandari, Hevi; Aisyah, Siti (Journal of Economics Research and Policy Studies, 2021)
The purpose of this study was to determine the effect of Gross Domestic Product (GRDP), Human Development Index, unemployment, and the amount of electricity consumption on poverty levels in the provinces of Java and Bali. The analysis model used is panel data regression. The type of data used in this study is secondary data in the form of panel data obtained from the publication data of the Central Bureau of Statistics (BPS) Java and Bali in 2011-2019. The results of this study indicate that the GRDP and the amount of electricity consumption have a negative and significant effect on poverty levels, the unemployment rate has a positive and significant effect on the poverty levels, and the Human Development Index has no effect on poverty levels.